2020
DOI: 10.1029/2019gl085623
|View full text |Cite
|
Sign up to set email alerts
|

Intraplate Volcanism and Regional Geodynamics in NE Asia Revealed by Anisotropic Rayleigh‐Wave Tomography

Abstract: Seismic structure related to the magmatic system beneath the potentially hazardous Changbaishan volcano recently becomes hotly debated. In addition, mantle flow dynamics throughout the back‐arc regions in NE Asia remain poorly constrained due to the lack of seismic data in the Korean Peninsula and surrounding ocean regions. In this study we construct a high‐resolution azimuthally anisotropic Rayleigh‐wave phase velocity model in NE Asia, by integrating seismic data from China, North Korea, South Korea, and Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 58 publications
(95 reference statements)
3
31
1
Order By: Relevance
“…Beneath the active Cenozoic magmatic province -CBM, high S-velocities at 15-35 km depths are observed in our model. This observation differs from the recent surface wave tomographic study of Fan et al (2020), in which they reported a slow Svelocity anomaly attributed to a potential lower-crustal magma reservoir below the CBM. We interpret the observed fast S-velocity underneath the CBM as the result of middle to lower-crustal magmatic intrusions (through cooling and solidification).…”
Section: Crustal Shear Velocity Anomaliescontrasting
confidence: 99%
See 1 more Smart Citation
“…Beneath the active Cenozoic magmatic province -CBM, high S-velocities at 15-35 km depths are observed in our model. This observation differs from the recent surface wave tomographic study of Fan et al (2020), in which they reported a slow Svelocity anomaly attributed to a potential lower-crustal magma reservoir below the CBM. We interpret the observed fast S-velocity underneath the CBM as the result of middle to lower-crustal magmatic intrusions (through cooling and solidification).…”
Section: Crustal Shear Velocity Anomaliescontrasting
confidence: 99%
“…Surface wave tomography (e.g., Fan et al, 2020Fan et al, , 2021Guo et al, 2016;Li et al, 2012Li et al, , 2013Pan et al, 2014Pan et al, , 2015 found a low velocity feature at lower-crustal depths under the CBM, upper-mantle low S-velocities and extremely thin lithosphere beneath the CBM, LXM and Sanjiang basin. Receiver function studies (e.g., He et al, 2013;Liu & Niu, 2011;Tao et al, 2014;Zhang et al, 2014;Zhang, Wu, Pan, et al, 2013) constrained crustal thicknesses and bulk Vp/Vs ratios across Northeast China, with crustal thicknesses ranging between 26 and 42 km while bulk Vp/Vs ratios varied between 1.60 and 1.88 (He et al, 2013;Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed a systematic investigation of the crustal structure and mantle anisotropy in the Afar region by means of receiver function and shear-wave splitting analyzes. Knowledge about the crustal thickness as well as crustal and lithospheric anisotropies (Legendre et al 2017(Legendre et al , 2020 can provide helpful insight into the crustal and mantle flow affecting the regional dynamics (Legendre et al 2016;Fan et al 2020). The main contribution of this study is a total of 431 new shear-wave splitting measurements in the region as well as 34 measurements of crustal thickness and ratio of seismic compressional and shear-wave velocities (V p /V s ).…”
Section: Tectonics Of the Afar Triple Junctionmentioning
confidence: 99%
“…We reveal that the SKS splitting measurements indicate anisotropy in two layers; the FPDs in the upper layer are NE‐SW (Figure 5c). Huang, Wang, et al (2011) also found similar NE‐SW FPDs at Station SNY, which was also revealed in the crust by P wave (Huang et al, 2014) and surface wave anisotropic tomography (Fan et al, 2020; Liu et al, 2016). The NE‐SW FPDs are different from the direction of Mesozoic lithospheric extension (Tian et al, 1992; Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 63%